Carbodiimide reagents for the chemical probing of RNA structure in cells - Wang, Peter Y. (RNA, 2019)
Deciphering the conformations of RNAs in their cellular environment allows identification of RNA elements with potentially functional roles within biological contexts. Insight into the conformation of RNA in cells has been achieved using chemical probes that were developed to react specifically with flexible RNA nucleotides, or the Watson–Crick face of single-stranded nucleotides. The most widely used probes are either selective SHAPE (2′-hydroxyl acylation and primer extension) reagents that probe nucleotide flexibility, or dimethyl sulfate (DMS), which probes the base-pairing at adenine and cytosine but is unable to interrogate guanine or uracil. The constitutively charged carbodiimide N-cyclohexyl-N′-(2-morpholinoethyl)carbodiimide metho-p-toluenesulfonate (CMC) is widely used for probing G and U nucleotides, but has not been established for probing RNA in cells. Here, we report the use of a smaller and conditionally charged reagent, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), as a chemical probe of RNA conformation, and the first reagent validated for structure probing of unpaired G and U nucleotides in intact cells. We showed that EDC demonstrates similar reactivity to CMC when probing transcripts in vitro. We found that EDC specifically reacted with accessible nucleotides in the 7SK noncoding RNA in intact cells. We probed structured regions within the Xist lncRNA with EDC and integrated these data with DMS probing data. Together, EDC and DMS allowed us to refine predicted structure models for the 3′ extension of repeat C within Xist. These results highlight how complementing DMS probing experiments with EDC allows the analysis of Watson–Crick base-pairing at all four nucleotides of RNAs in their cellular context.